Which visual acuity measurements define high-quality care for patients with neovascular age-related macular degeneration treated with ranibizumab? - Ross, A; Donachie, P; Sallam, A; Stratton, I; Mohamed, Q; Scanlon, P; Kirkpatrick, J; Johnston, R (2013)
PURPOSE: The purpose of this study is to define which visual acuity (VA) measurements are the best indicators of high-quality care for patients receiving intravitreal ranibizumab for neovascular age-related macular degeneration (nAMD). METHODS: Analysis of prospectively collected data recorded within an electronic medical record system on treatment-naive, first-eligible eyes with nAMD, treated with ranibizumab using an as-needed treatment regimen with a minimum follow-up of 1 year. Data collection included the following: age, gender, laterality, type of nAMD, VA, central 1 mm OCT retinal thickness, number of intravitreal injections, and number of follow-up assessments. RESULTS: Data were available on the first-treated eye from 406 patients with at least 1 year follow-up; of these, 198 had data at 2 years. The mean baseline VA of 54.4 Early Treatment Diabetic Retinopathy Study letters improved to 58.5 letters at 12 months and to 56.8 letters at 24 months. The mean VA changes from baseline to 1 year were +6.5, +7.5, +1.7, and -1.5 letters, respectively, for baseline VA categories of 23-35, 36-55, 56-70, and >70 letters. Change in mean VA from the end of the loading phase to year 1 ranged from -2.9 to +1.4 letters for the different baseline VA categories. The mean number of injections were similar across baseline VA categories ranging from 5.7 to 6.0 injections in year 1 and from 3.3 to 3.8 in year 2. CONCLUSIONS: This large, real-world series demonstrates that mean change in VA is largely a function of selection criteria and baseline VA. The quality of a service is therefore better judged by actual VA outcomes and maintenance of vision after the loading phase.